OPTIMALISASI POLA PARKIR DI UNIVERSITAS BANDAR LAMPUNG - Munawaroh, Ai Siti; Syarkowi, Muhar (Jurnal Ilmiah Teknik Sipil; Vol 25 No 2 (2021): Jurnal Ilmiah Teknik Sipil, Vol. 25 No. 2, Juli 2021, 2022)
The increasing number of students at Universitas  Bandar Lampung (UBL) causes increasing the number of vehicle movements. The purpose of the research is to: 1) find out the parking characteristics in the UBL and 2) find out the optimization of parking patterns in the UBL. The method used in this study is cualitative method. Data retrieval is done by conducting surveys and measurements related to the number of vehicles. Analysis is done by comparing the formula and designing the parking pattern. The results of the study obtained maximum parking accumulation of 18 cars and 177 motorcycles with an accumulation of the average car 14.51 and 154.675. The average duration of the car is 2.07 and the motor is 54.45. The maximum parking volume is 15 cars and 98 motorcycles. The car PTO is 0.21 and the motor is 0.19. The maximum parking index of the car is 130% and the motor is 148.90%. Parking Requirements (NP) 70 parking lots and 815 parking lots. The optimal parking pattern for cars at the UBL Campus is an angled parking pattern forming an angle of 60 °. With this parking pattern can add 18 cars. The optimal parking pattern used in the motorcycle parking area is a 90 ° angle. This parking pattern can accommodate more than 63 motorcycles compared to the previous parking pattern.